Clinicopathological characteristics of patients with ovarian carcinoma in a tertiary care center of the sub-himalayan region: An ambispective study - Hanumanthappa Sunil; Jaya Chaturvedi; Sunil K Singh; Bodhisattva Bose; Pratik Solanki; Avijit Mondal; Deepak Sundriyal; Prashant Durgapal; Anupama Bahadur; Amit Gupta (Wolters Kluwer Medknow Publications, 2023)
Background and Objective: The ovary is considered one of the complex organs with respect to histology, embryology, steroidogenesis, as well as tumor incidence. In order to attain a better knowledge of the disease mechanism, the current research highlights a correlation between the pathological and clinical features of epithelial ovarian carcinoma. The aim of this research is to evaluate the oncological and clinicopathological results of patients who were diagnosed with ovarian cancer (OC) in a tertiary care center situated in the Sub-Himalayan region. Materials and Methods: Seventy patients with OC registered at the department of surgical oncology, obstetrics and gynecology, and medical oncology between January 2019 and December 2021 had been estimated in this prospective and retrospective observational research. Age, histological type, stage at presentation, and treatment pattern were the characteristics examined in the patients. Results: The patients' average age was 48.18 ± 12.309 years, having a maximum age of 74 years as well as the minimum age of 21 years. The most frequent symptom was abdominal pain (30%). Hypertension was the most commonly seen comorbidity in 7 (10%) patients. Most of the patients had high-grade serous carcinoma in 40 (56.1%) patients. Neoadjuvant chemotherapy and adjuvant type of chemotherapy were given to 30 (42.9%) patients. After 3 months, follow-up imaging showed that there was no residual disease in 51 (72.8%) patients, and the disease progression was seen in 8 (11.4%) patients. Conclusion: Because of their clinical correlation, behavioral predictability, as well as proper management of patient care, the right clinicopathological detection of ovarian tumors is extremely important.